Pengaruh Keputusan Keuangan dan Struktur Kepemilikan terhadap Nilai Perusahaan - Akbar, Muhammad; Hindasah, Lela (Journal of Accounting and Investment, 2007)
This  research examines the effect of  financial decision (debt policy, dividend policy and investment)  and  ownership structure (insider ownership and institutional ownership) to  firm value. This study  used  96 firm-year samples of firms listed  in Indonesian Stock Exchange during 2002 until 2006. Data are analyzed using multivariate regression method. The result of this research indicated that the debt policy, dividend policy, insider ownership  are not  significantly affect to  the firm value. The effect of investment  to firm value is positively  significant but  institutional ownweship is negatively significant.